The difference in the intraday return-volume relationships of spot and futures: A quantile regression approach - Jaeram Lee; Geul Lee; Doojin Ryu (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This study illuminates the difference in the intraday return-volume relationships of spot and index futures. The quantile regression analyses show that the widening effect of the spot trading volume on the distribution of spot returns disappears within a short period of time, whereas that of the futures trading volume on the distribution of spot returns remains over the relatively long term. The short-term effect of the spot volume and the long-term effect of the futures volume are consistent for trading volume shocks. The findings suggest that the spot volume is primarily induced by the demand for hedging or differences of opinion, whereas the futures volume contains information about price movements.
http://dx.doi.org/10.7910/DVN/MCOVPQ
Keywords: C22; G12; G14; 330; index futures; information channel; intraday information content; option- implied volatility; quantile regression; return-volume relationship